Adoptive cell therapy using tumor‐infiltrating lymphocytes for melanoma refractory to immune‐checkpoint inhibitors. Issue 8 (30th June 2021) - Hirai, Ikuko; Funakoshi, Takeru; Kamijuku, Hajime; Fukuda, Keitaro; Mori, Mariko; Sakurai, Masatoshi; Koda, Yuya; Kato, Jun; Mori, Takehiko; Watanabe, Naohide; Noji, Shinobu; Yaguchi, Tomonori; et al.
Abstract: To evaluate the feasibility of adoptive cell therapy (ACT) using ex vivo‐expanded tumor‐infiltrating lymphocytes (TILs) in Japanese patients with melanoma who failed immune‐checkpoint inhibitor therapy, an open‐label, single‐arm, pilot study was conducted. We investigated the immunological and genetic factors of the pretreatment tumor and expanded TILs that may be associated with the clinical response. The treatment protocol comprised preparation of TIL culture, lympho‐depleting non‐myeloablative preconditioning with cyclophosphamide and fludarabine, TIL infusion, and intravenous administration of low‐dose IL‐2. Three patients of clinical subtypes mucosal, superficial spreading, and acral melanoma underwent TIL‐ACT. Most severe adverse events, including fever and leukopenia, were manageable with the supportive regimen specified in the protocol, suggesting that the TIL‐ACT regimen is suitable for Japanese patients with melanoma. One patient showed a short‐term partial response, one relatively long‐stable disease, and one experienced disease progression. Whole‐exome and transcriptional sequencing of isolated tumor cells and immunohistochemical analyses before TIL‐ACT revealed various immunostimulatory factors, including a high tumor mutation burden and immune cell‐recruiting chemokines, as well as various immunosuppressive factors including TGF‐β, VEGF, Wnt/β‐catenin, and MAPK signaling and epithelial‐to‐mesenchymal transition, which might influence the efficacy of TIL‐ACT. Our results imply mechanisms for the antitumor effect of and resistance to TIL‐ACT. Further studies of immune‐resistant mechanisms of TIL‐ACT are warranted. This study is registered with the UMIN Clinical Trial Registry (UMIN 000011431). Abstract : Various factors involved in the balance of immunostimulation and immunosuppression are important in the TIL‐ACT response for melanoma patients.